(untitled) (Orinoquia, 2014)
High demand for conventional raw materials for food’s manufacture makes everyday costs rise, causing 70% of the production costs are for food, making it necessary to look for alternative sources for an efficient fish farming. The objective was to determine apparent digestibility coefficients (ADC) of Tithonia Diversifolia, Gliricidia Sepium and Cratylia Argentea in young cachama. 400 cachamass were selected with an average weight of 125 g, which were divided into 4 groups. To collect feces nine fiberglass tanks were used with 200 L capacity with conical bottom (modified Guelph system). The apparent digestibility coefficients (ADC) of the ingredients were determined by indirect method. The experimental diets were composed of 69.5% Dietary Reference (DR), 0.5% inert marker (Cr2O3) and 30% leaf meal of raw material to be evaluated. The CDA protein was to 54.22% Gliricidia, Tithonia Diversifolia: 35.7% and 23.9% Cratylia Argemtea. The leaf meal Gliricidia is an alternative raw material that can be used in cachama, for good percentage of crude protein 26.55%, plus the ability to use 54.2% (CDA), which equivalent to a protein digestibility of 14.39%, considering that this species has a requirement of 32% protein.